2011
DOI: 10.1021/je200536h
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methylene Blue from Aqueous Solution with Activated Carbon/Cobalt Ferrite/Alginate Composite Beads: Kinetics, Isotherms, and Thermodynamics

Abstract: In this study, we have demonstrated a simple ionic polymerization route for the fabrication of a magnetically separable adsorbent, that is, activated carbon/cobalt ferrite/alginate composite beads, for effective dye removal from aqueous solution. Adsorption characteristics of the as-fabricated magnetic beads were assessed by using methylene blue (MB) as an adsorbate. The isotherms, kinetics, and thermodynamics of the adsorption of MB onto the magnetic beads have been studied at various experimental conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
131
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(143 citation statements)
references
References 57 publications
12
131
0
Order By: Relevance
“…Moreover, the initial adsorption rate h (mg/g¨min) increased with the increase of dye concentration, which is due to the existence of a large number of active sites on the adsorbent. Furthermore, the rate constant (k 2 ) decreased with the increasing initial MV concentrations, which was attributed to the striking hindrance of higher concentrations of MV [43]. All the illustrations mentioned above showed that the adsorption of MV onto α-Fe 2 O 3 @PHCMs followed the pseudo-second-order kinetic model well, and the chemical sorption might be involved in the adsorption process, which was similar to the results reported by Li's group [15].…”
Section: Adsorption Kineticssupporting
confidence: 85%
“…Moreover, the initial adsorption rate h (mg/g¨min) increased with the increase of dye concentration, which is due to the existence of a large number of active sites on the adsorbent. Furthermore, the rate constant (k 2 ) decreased with the increasing initial MV concentrations, which was attributed to the striking hindrance of higher concentrations of MV [43]. All the illustrations mentioned above showed that the adsorption of MV onto α-Fe 2 O 3 @PHCMs followed the pseudo-second-order kinetic model well, and the chemical sorption might be involved in the adsorption process, which was similar to the results reported by Li's group [15].…”
Section: Adsorption Kineticssupporting
confidence: 85%
“…Adsorption and desorption of the solute and the solvent molecules take place simultaneously, and the adsorption process involves energy changes that could result in a positive ΔH 0 . In addition, the positive 45 value of ΔS 0 confi rms that the good affi nity 46 of MO towards the activated carbon and the increased randomness at the solid-solution interface during the adsorption process of MO on to PJBC.…”
Section: Adsorption Thermodynamicsmentioning
confidence: 87%
“…For porous sorbents such as activated carbons, diffusion effects may be quite important and so the physical meaning of the evaluated rate constant must be determined in order to be able to know the mass transfer mechanism involved [42,43]. Most commonly, the rate of adsorption is controlled by film diffusion or intra-particle diffusion or both [21,44,45].…”
Section: Adsorption Mechanismmentioning
confidence: 99%